Cyclic Vomiting Syndrome in the Emergency Department: A 10-Year Review of Clinical Presentation and Management. Issue 10 (12th October 2022) - Beals, Lauren; Sarjinsky, Sharon; Faltyn, Mateusz; Issenman, Robert M.; Kam, April J.
Abstract : Objectives: The aims of the study were (1) to determine how frequently patients with cyclic vomiting syndrome (CVS) present to the pediatric emergency department (ED) with CVS-related symptoms, (2) to identify variables in clinical presentation that occur frequently in patients with multiple ED visits, and (3) to compare ED management of CVS with recommended guidelines. Methods: This study is a retrospective chart review of all ED visits for CVS between April 1, 2008, and April 1, 2018, at a single center. Patients were identified from a master list of patients diagnosed with CVS in a pediatric gastroenterology clinic at the same center between June 1, 2004, and June 19, 2018. Results: Of the 181 CVS clinic patients identified, 65 had visited to the ED (35.9%). Two hundred twenty-eight visits met inclusion criteria. A total of 42.5% of these visits were made by a small number of high-intensity patients (n = 6) who had an average of 16.1 visits each. These patients represented less than 10% of the total patient group. Patients with frequent visits had longer visits (536.52 vs 380.55 minutes), more frequent hospital admissions (57.73% vs 29.01%), and more visits to the ED before a formal diagnosis of CVS was made (5.83 vs 1.22), but few other distinguishing characteristics. Only 27% of eligible visits were managed with an available order set, and management varied from recommended guidelines. Conclusions: An ambiguous presentation makes the identification and consistent management of CVS in the ED difficult. Physicians should consider CVS for patients who present multiple times with unremitting vomiting to ensure appropriate referral for diagnosis and prophylactic treatment. Future studies are warranted to evaluate anticipatory processing and treatment of the "high-intensity patients" who account for much of the clinical morbidity and resource utilization.